Plasma phospholipidome analysis reveals a different profile between children with phenylketonuria and healthy children - Guerra, Inês Maria dos Santos (2022)
Phenylketonuria (PKU) is the most prevalent innate error in amino acid metabolism. PKU is characterized by the deficiency of a phenylalanine (Phe) metabolism enzyme, phenylalanine hydroxylase, which is responsible for the conversion of Phe into tyrosine (Tyr). Deficiency of this enzyme causes the accumulation of Phe, which may cause severe cognitive impairment. Early diagnosis through neonatal screening and a rapid therapeutic implementation are essential to prevent irreversible sequelae. Therapeutic approach for PKU is based on strict control of Phe intake through a lifelong diet restricted in proteinrich food. High dietary restrictions can lead to imbalances in other nutrients, notably lipids. Previous plasma/serum and red blood cells studies of PKU patients with Phe-restricted diet revealed lipid changes, namely in lipoprotein’s components and fatty acid profile. Despite the changes already reported, further studies are needed to understand in detail the changes in the lipid profile of PKU patients, particularly at the level of phospholipids, which also have important signalling and regulatory functions. Thus, the main aim of this work was to study the phenylketonuric phospholipidome in order to identify the occurrence of changes in lipid profile. To this end, the plasma phospholipidenriched extracts obtained from PKU and healthy children (control group, CT) were analysed by HILIC-MS/MS and GC-MS. Using this approach, 187 lipid species belonging to 9 different phospholipid classes and 3 ceramides were identified. Principal component analysis of lipid species dataset showed a distinction between PKU and CT groups. Univariate analysis revealed that 146 phospholipid species were significantly different between groups. The species with major variation included phosphatidylcholines (PC), bearing polyunsaturated fatty acids (PUFA), which were more abundant in the PKU group. For patients with diet supplemented with PUFA, the higher level of PUFA-containing lipid species may be related with such supplementation. This study was the first report comparing the plasma polar lipidome of PKU and healthy children, highlighting that the phospholipidome of PKU children is significantly altered when compared with healthy children. In conclusion, the lipidomic approach used in this work allowed the analysis and identification of the phospholipid profile of PKU and healthy children. However, further studies with larger cohorts are needed to clarify if the changes identified are specific to the phenylketonuric children, namely those with PUFA supplementation.